Properties and Microstructure Distribution of High-Performance Thermal Insulation Concrete - Malek Mohammad (17150977) (2020)
The aim of this experimental study is to develop high strength and lightweight concrete mixture suitable for structural applications. This work investigates the effect of replacing normal aggregate either partially or totally with expanded perlite aggregate. This material allows for better thermal insulation properties, thus decreasing the energy usage within the life cycle of the concrete structure. Expanded perlite aggregate was used in concrete by 20%, 40%, 60%, 80%, and 100% in replacement of the natural aggregate. Material characterization tests of compressive strength, flexural strength, and thermal conductivity were carried out for six concrete mixtures. In addition, microstructure analysis was performed with the aid of a micro-computed tomography system to investigate the effects and relation of microstructure quantities on material properties. The proposed concrete mixture, which has 100% of expanded perlite aggregate, has a unit weight of 1703 kg/m3 and achieved reduction percentage of thermal conductivity around 62% (1.81 to 0.69 W·m−1·K−1) and a compressive strength of 42 MPa at 28 days; and thus is ideal for structural applications with enhanced properties. Other Information Published in: Materials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ma13092091